기계 상태진단을 위한 인-라인형 오일 모니터링 스마트 센서 - 공호성; C.V. Ossia; 한흥구; L. Markova (한국트라이볼로지학회, 2008)
An integrated in-line oil monitoring detector assigned for continuous in situ monitoring multiple parameters of oil performance for predicting economically optimal oil change intervals and equipment condition control is presented in this study. The detector estimates oil deterioration based on the information about chemical degradation, total contamination, water content of oil and oil temperature. The oil oxidation is estimated by “chromatic ratio”, total contamination is measured by the changes in optical intensity of oil in three optical wavebands (“Red”, “Green” and “Blue”) and water content is evaluated as Relative Saturation of oil by water. The detector is able to monitor oils with low light absorption (hydraulic, transformer, turbine, compressor and etc. oils as well as oils with rather high light absorption in visible waveband (diesel and etc. oils). In a case study that the detector is applied to a diesel engine oil, it is found that the detector provides good results on oil chemical degradation as well as soot concentration